THE EFFECT OF EMPLOYEE COMPETENCE, MANAGEMENT INFORMATION SYSTEMS, AND PARTICIPATORY LEADERSHIP ON EMPLOYEE PERFORMANCE AT THE KEPRI PROVINCIAL GOVERNMENT PUBLIC WORKS AND PUBLIC HOUSING AGENCYTHROUGH ORGANIZATIONAL COMMITMENT - Trio Ardhimansyah; Chablullah Wibisono; Sri Yanti (RADJA PUBLIKA, 2025)
This study aims to analyze the influence of employee competence, management information systems, and participative leadership on employee performance at the Public Works, Spatial Planning, and Land Agency (PUPRP) of the Riau Islands Provincial Government, with organizational commitment as a mediating variable. The research is motivated by the strategic role of PUPRP in infrastructure development and spatial planning, which requires optimal employee performance. The study employs a quantitative approach with data collected through questionnaires distributed to civil servants within the agency. The analysis uses Structural Equation Modeling (SEM) to test both direct and indirect effects of the independent variables on employee performance. The results indicate that employee competence, management information systems, and participative leadership significantly influence employee performance. Furthermore, organizational commitment partially mediates the relationship between these variables and employee performance. The findings highlight the importance of enhancing employee competence through continuous training, optimizing management information systems, and implementing participative leadership to improve organizational performance. These results provide practical recommendations for government institutions to develop strategies that strengthen organizational commitment and foster sustainable performance improvement.